Hybrid governance, organisations and society value creation perspectives - Johanson, Jan-Erik; Vakkuri, Jarmo (London Routledge, Taylor & Francis Group, 2021)
The era of hybrid governance is here. More and more organizations occupy a position between public and private ownership. And value is created not through business or public interests alone, but through distinct forms of hybrid governance. National governments are looking to transform their administrative systems to become more business driven. Likewise, private enterprises are seeing value gains in promoting public interest in their corporate social responsibility programs.

But how can we conceptualize, evaluate and measure the value and performance of hybrid governance and organizations? This book offers a comprehensive overview of how hybrids produce value. It explores the drivers, obstacles and complications for value creation in different hybrid contexts: state-owned enterprises, urban policy-making, universities and non-profits from around the world. The authors address several types of value contents, for instance financial, social and public value. Furthermore, the book provides a novel way of understanding multiple forms of doing value in hybrid settings. The book explains mixing, compromising and legitimising as important mechanisms of value creation.

Aimed at researchers and students of public management, public administration, business management, corporate social responsibility and governance, this book provides a theoretical, conceptual and empirical understanding of value creation in hybrid organizations. It is also an invaluable overview of performance evaluation and measurement systems and practices in hybrid organizations and governance.
Value creation among hybrids/ Jarmo Vakkuri and Jan-Erik Johanson -- The quest for value creation in state-owned enterprises / Joaquim Rubens Fontes-Filho and Márcia Cristina Carris de Almeida -Nested hybridity and value definition in public higher education: a conceptual view/ Elias Pekkola, Rómulo Miguel Pinheiro, Lars Geschwind, Taru Siekkinen, Teresa Carvalho and Kirsi Pulkkinen -- Integrating the private economy with the public transport sector in China/ Guangjian Xu and Qianqian Lu -- Temporary organisations as hybrids: Challenges and mechanisms for public value creation/ Sebastian Godenhjelm and Stefan Sjöblom -- Multiplicity of values in measuring performance of hybrids: the case of social care/ Cristina Campanale, Lino Cinquini and Giuseppe Grossi -- Performance goals as boundary objects: A compromise between different value definitions in hybrids/ Tomi Rajala -- Complexity of value proposition in hybrids: The Japanese experience/ Tomoe Katoh -- Value that matters: Expansive and restrictive hybridity in public-private pension schemes/ Ville-Pekka Sorsa -- The Hybrid state of public universities in Austria/ Michael Habersam, Martin Piber and Matti Skoog -- Value creation by two types of hybrid organizations: opportunities and risks/ Philip Marcel Karré -- Value creation between and among levels of hybrid governance/ Jan-Erik Johanson and Jarmo Vakkuri.
Includes bibliographical references and index.
Keywords: Public-private sector cooperation -- Management